“Role Of Shatavaryadi Churna On Rajonivrutti Avastha With Special Reference To Postmenopausal Syndrome”- A Review Of Literature - Kumar, Suresh; Gopal, Brij; choudhary, Dharmendra (International Research Journal of Ayurveda & Yoga, 2021)
The menopause is permanent cessation of menstruation at the end of reproductive life due to loss of ovarian follicular activity. Woman has a vital role in each and every family as well as for the society. Now a day’s they handle their family along with their professional life successfully. But still now they are struggling to be fit in late 50s or earlier. In late reproductive stage, they experience so many symptoms that disturbances their daily life, hampered physically and mentally. So it’s very important to restore their healthy life. Postmenopausal Syndrome include Hot flushes, irritability, mood swings, insomnia, dry vagina, difficulty concentrating, mental confusion, stress incontinence, urge incontinence, osteoporotic symptoms, depression, headache etc.In Ayurveda, this phenomenon is considered as a natural process due to aging and not associated with any serious health problems. Menopause is a state of Vata predominance & Dhatukshaya and it occurs at the age of 50 years. ‘Shatavaryadi Churna’ is effective in the management of Postmenopausal Syndrome and effective, safe, promising and cost effective remedy. Acharya Sushruta mentioned menopause as Jarapakvaavastha (geriatric age) of the body, drugs with Rasayana (rejuvenation) property are very much applicable in this geriatric age.